2021
DOI: 10.1108/jsma-02-2021-0049
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation and entrepreneurship process in SMEs of India: a moderating role of adoption of AI-CRM capability and strategic planning

Abstract: PurposeThe purpose of this study is to identify the determinants that could impact corporate digital entrepreneurship for the small and medium enterprises (SMEs) of India. The study also investigates the moderating role that adopting artificial intelligence (AI)-customer relationship management (CRM) capability and strategic planning has in corporate digital entrepreneurship.Design/methodology/approachWith the inputs from literature and theories, a model has been developed conceptually. The model has been vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 77 publications
5
65
0
Order By: Relevance
“…Studies have found that SMEs apply AI technologies to help them remodel various business activities such as supply chain networks, production systems, and operational management systems [43,44]. SMEs can remodel business applications with the help of AI technology according to their needs without incurring much cost [45].…”
Section: Ai-enabled Applications (Aea)mentioning
confidence: 99%
“…Studies have found that SMEs apply AI technologies to help them remodel various business activities such as supply chain networks, production systems, and operational management systems [43,44]. SMEs can remodel business applications with the help of AI technology according to their needs without incurring much cost [45].…”
Section: Ai-enabled Applications (Aea)mentioning
confidence: 99%
“…In addition, we return to the TAM literature ( Davis et al., 1989 ), to further consider how the perceived usefulness of an innovation is conditioned by its associated ease of use, as shown in the extensive review by Gefen and Straub (2000) and confirmed in numerous digital contexts in recent years, such as digital entrepreneurship in SMEs ( Chatterjee et al., 2021 ). In the latter case, P. V. Nguyen et al.…”
Section: Literaturementioning
confidence: 99%
“…The fifth article, "Digital transformation and entrepreneurship process in SMEs of India: a moderating role of adoption of AI-CRM capability and strategic planning" by Chatterjee et al (2022), investigates the factors affecting corporate digital entrepreneurship of SMEs in India and the moderating effect of adopting AI-customer relationship management (CRM) capability and strategic planning. The research provides evidence that perceived usefulness, perceived ease of use and willingness to change have strong and significant effects on corporate digital entrepreneurship as well as the two moderators have significant impacts on the relationships between corporate digital entrepreneurship and its predictors.…”
Section: Articles In the Simentioning
confidence: 99%